Buenos practica para la produccion tradicional de semilla de papa de calidad - PRO INPA (Bioversity International, 2016)
The training manual gives an overview of the diversity of potatoe and in Bolivia. It also highlights the importance of the traditional /local seed system in providing over 95% of potato seed. The manual provided best practices and innovative approaches for maintaining quality seed of potatoes in then the local seed system. It also outlines the crucial steps in the selection of quality seed; production of quality seed and quality assurance mechanisms for potatoe seed.